Water vapor heterogeneity related to tropopause folds over the North Atlantic revealed by airborne water vapor differential absorption lidar - Flentje, H.; Dörnbrack, A.; Ehret, G.; Fix, A.; Kiemle, C.; Poberaj, G.; Wirth, M. (Journal of Geophysical Research, 2005)
Airborne differential absorption lidar (DIAL) measurements of tropospheric water vapor and aerosol/clouds are presented from transfers across the North Atlantic on 13–15 May and 16–18 June 2002. The intense dynamical activity over the Atlantic is reflected in complex structures like deep tropopause folds, extended dry layers, and tilted aerosol filaments. Intrusions with H2O mixing ratios below 0.03 g kg−1 regularly develop along the storm track over intense cyclones and correspond to analyzed (European Centre for Medium-Range Weather Forecasts (ECMWF)) or simulated (MM5) potential vorticity anomalies. Sloping folds are typically 1 km thick in vertical profiles but on horizontal sections resemble long filaments with widths of a few hundred kilometers. Filaments of solid, roughly micron-sized particles occur inside and along the axes of the tropopause folds. The particles most likely originate in forest fires, from where they are injected to the lower stratosphere by deep convection and later on reenter the troposphere in developing baroclinic disturbances. Their laminar appearance indicates that these intrusions have not yet been mixed but are eroded on timescales significantly larger than a few days by stretching-thinning, stirring, and only finally, turbulent diffusion. MM5 mesoscale model simulations and, with less accuracy, also ECMWF analyses are capable of reproducing the dynamical structures associated with the observed dry intrusions. However, deep inside the intrusions where scales are small, even the MM5-simulated water vapor mixing ratios are more than twice those observed. The large dynamical range of water vapor mixing ratios (3 orders of magnitude) and large gradients (>2 g kg−1 km−1 at the intrusions' boundaries) constitute a challenge for future space-borne water vapor DIAL systems.